Phosphorus and humic acid extraction from fermentation liquor of ferric phosphate sludge via layered double hydroxides: Efficiency and interaction mechanism. (15th October 2021) - Yan, Hanlu; Fu, Yuling; Liao, Xueke; Chen, Qiuwen; Wang, Zhiyuan; Chen, Cheng; Shih, Kaimin
Abstract: Iron salts are increasingly employed in wastewater treatment worldwide, generating ferric phosphate sludge with low phosphorus (P) bioavailability. The fermentation of ferric phosphate sludge effectively transfers P from the solid phase to the liquid phase and simultaneously releases high contents of ferrous cations (Fe 2+ ) and humic acids (HA) into the sludge liquor. This study aimed to extract P from simulated and real sludge fermentation liquor via Mg/Al layered double hydroxide (LDH), evaluate the impact of co-existed Fe and explore the interaction mechanism between phosphate and HA adsorption. The Fe influence experiments explored the suitable organic matter concentration range for the LDH adsorbent to extract P without the concurrent precipitation of iron compounds. Thus, the residual ferrous species in sludge liquor can be reused as a flocculant. Moreover, the analysis of the adsorption kinetics of phosphate at 25, 35, and 55 °C showed that increasing temperature accelerated the phosphate adsorption rate but had minor effects on the P adsorption capacity. HA and phosphate were jointly adsorbed onto Mg/Al LDH. Investigations on isotherm, kinetics, and mechanism suggested that phosphate anions have a competitive advantage in the ion exchange process but are hindered by large-molecular-weight HA in surface adsorption because of limited adsorption sites. Subsequent adsorption experiments in sludge liquor and nutrient release test confirmed the possibility of using Mg/Al LDH to simultaneously recover P and organic matters from sludge fermentation liquid based on its stable P adsorption performance and intercalated anion slow-release property. Graphical abstract: Image 1 Highlights: Phosphate has a competitive advantage in ion exchange process against humic acids. Concentrated acetate ions hinder phosphate sorption via competitive intercalation. Used adsorbent shows slow-releasing properties of phosphorus and humic acids.